Arbuscular Mycorrhiza and Nitrification: Disentangling Processes and Players by Using Synthetic Nitrification Inhibitors - Dudáš, Martin; Pjevac, Petra; Kotianová, Michala; Gančarčíková, Kateřina; Rozmoš, Martin; Hršelová, Hana; Bukovská, Petra; Jansa, Jan (Applied and environmental microbiology, 2022)
Both plants and their associated arbuscular mycorrhizal (AM) fungi require nitrogen (N) for their metabolism and growth. This can result in both positive and negative effects of AM symbiosis on plant N nutrition. Either way, the demand for and efficiency of uptake of mineral N from the soil by mycorrhizal plants are often higher than those of nonmycorrhizal plants. In consequence, the symbiosis of plants with AM fungi exerts important feedbacks on soil processes in general and N cycling in particular. Here, we investigated the role of the AM symbiosis in N uptake by Andropogon gerardii from an organic source (15N-labeled plant litter) that was provided beyond the direct reach of roots. In addition, we tested if pathways of 15N uptake from litter by mycorrhizal hyphae were affected by amendment with different synthetic nitrification inhibitors (dicyandiamide [DCD], nitrapyrin, or 3,4-dimethylpyrazole phosphate [DMPP]). We observed efficient acquisition of 15N by mycorrhizal plants through the mycorrhizal pathway, independent of nitrification inhibitors. These results were in stark contrast to 15N uptake by nonmycorrhizal plants, which generally took up much less 15N, and the uptake was further suppressed by nitrapyrin or DMPP amendments. Quantitative real-time PCR analyses showed that bacteria involved in the rate-limiting step of nitrification, ammonia oxidation, were suppressed similarly by the presence of AM fungi and by nitrapyrin or DMPP (but not DCD) amendments. On the other hand, abundances of ammonia-oxidizing archaea were not strongly affected by either the AM fungi or the nitrification inhibitors. IMPORTANCE Nitrogen is one of the most important elements for all life on Earth. In soil, N is present in various chemical forms and is fiercely competed for by various microorganisms as well as plants. Here, we address competition for reduced N (ammonia) between ammonia-oxidizing prokaryotes and arbuscular mycorrhizal fungi. These two functionally important groups of soil microorganisms, participating in nitrification and plant mineral nutrient acquisition, respectively, have often been studied in separation in the past. Here, we showed, using various biochemical and molecular approaches, that the fungi systematically suppress ammonia-oxidizing bacteria to an extent similar to that of some widely used synthetic nitrification inhibitors, whereas they have only a limited impact on abundance of ammonia-oxidizing archaea. Competition for free ammonium is a plausible explanation here, but it is also possible that the fungi produce some compounds acting as so-called biological nitrification inhibitors.
Keywords: Mycorrhizae; isotopic (15N) labeling and tracing; amplicon sequencing; Ammonia; Nitrification; Nitrogen; ammonia-oxidizing bacteria; Plant Roots; amoniové sloučeniny; Rhizophagus irregularis; Ammonium Compounds; Soil Microbiology; Soil; nitrifikace; arbuscular mycorrhiza; kořeny rostlin; Dimethylphenylpiperazinium Iodide; quantitative real-time PCR; jodid dimethylfenylpiperazinia; Archaea; amoniak; dusík; půdní mikrobiologie; půda; mykorhiza; synthetic nitrification inhibitor; ammonia-oxidizing archaea